Can malaria rapid diagnostic tests by drug sellers under field conditions classify children 5 years old or less with or without Plasmodium falciparum malaria? Comparison with nested PCR analysis - Kitutu, Freddy Eric; Wamani, Henry; Selling, Katarina Ekholm; Ashaba Katabazi, Fred; Bisaso Kuteesa, Ronald; Peterson, Stefan (Malaria journal, 2018)
Malaria rapid diagnostic tests (RDTs) available as dipsticks or strips, are simple to perform, easily interpretable and do not require electricity nor infrastructural investment. Correct interpretation of and compliance with the RDT results is a challenge to drug sellers. Thus, drug seller interpretation of RDT strips was compared with laboratory scientist re-reading, and PCR analysis of Plasmodium DNA extracted from RDT nitrocellulose strips and fast transient analysis (FTA) cards. Malaria RDT cassettes were also assessed as a potential source of Plasmodium DNA. Methods: A total of 212 children aged between 2 and 60 months, 199 of whom had complete records at two study drug shops in south western Uganda participated in the study. Duplicate 5 μL samples of capillary blood were picked from the 212 children, dispensed onto the sample well of the CareStart™ Pf-HRP2 RDT cassette and a FTA, Whatman™ 3MM filter paper in parallel. The RDT strip was interpreted by the drug seller within 15–20 min, visually re-read centrally by laboratory scientist and from it; Plasmodium DNA was recovered and detected by PCR, and compared with FTA recovered P. falciparum DNA PCR detection. Results: Malaria positive samples were 62/199 (31.2%, 95% CI 24.9, 38.3) by drug seller interpretation of RDT strip, 59/212 (27.8%, 95% CI 22.2, 34.3) by laboratory scientist, 55/212 (25.9%, 95% CI 20.0, 32.6) by RDT nitrocellulose strip PCR and 64/212 (30.2%, 95% CI 24.4, 37.7). The overall agreement between the drug seller interpretation and laboratory scientist re-reading of the RDT strip was 93.0% with kappa value of 0.84 (95% CI 0.75, 0.92). The drug seller compliance with the reported RDT results was 92.5%. The performance of the three diagnostic strategies compared with FTA-PCR as the gold standard had sensitivity between 76.6 and 86.9%, specificity above 90%, positive predictive values ranging from 79.0 to 89.8% and negative predictive values above 90%. Conclusion: Drug sellers can use RDTs in field conditions and achieve acceptable accuracy for malaria diagnosis, and they comply with the RDT results. Plasmodium DNA can be recovered from RDT nitrocellulose strips even in the context of drug shops. Future malaria surveillance and diagnostic quality control studies with RDT cassette as a source of Plasmodium DNA are recommended.
Keywords: Integrated case management; Rapid diagnostic test; Polymerase chain reaction; Drug seller; Uganda; Febrile illness; Malaria; Private sector; Compliance; External quality assurance